11. EFEK PENAMBAHAN AMPAS KEDELAI YANG DIFERMENTASI DENGAN Aspergillus niger DALAM RANSUM TERHADAP HISTOMORFOMETRI VILI USUS HALUS AYAM KAMPUNG (Gallus domesticus) The Effect of Aspergillus niger-Fermented Soybean Residue Supplementation in Ration the Histomophometry of Local Chicken (Gallus domesticus) Small Intestine - Masyitah Nafli Sari (Universitas Syiah Kuala, 2016)
The aim of this research was to find out the effect of Aspergillus niger-fermented soybean residue in ration on the histomorphometry of the small intestine villi of local chickens (Gallus domesticus).This study used a completely randomized design. Nine female chicken aged 15-16 months were divided into three groups. Each group consisted of three chikens. All chicken were given 324-2 ration and water ad libitum. Group P1 (control group) was given 100 g ration each day, group P2 was given a combination of 85 g ration and 10 g unfermented soybean residue everyday whereas group P3 was given 85 g ration and 10 g Aspergillus niger-fermented soybean residue everyday. Treatment was performed for 30 days. On day 31, chickens were slaughtered and subsequently three parts of the small intestine that consists of duodenum, jejunum, and ileum were collected and fixed in 10% neutral buffered formaline (NBF) solution for histological preparation. To measure the surface area of three regions of intestine, all histological sections were stained with Masson’s trichrome Goldner's modification. Based on the statistical analysis, there was no difference in height of villi among three parts of small intestine (P0.05), but there were statistical different (P0,05) in ileum basal and duodenum apical width of three groups after supplementation with fermented soybean residue and non-fermented. Based on the results of this experiment, it could be conluded that supplementation non-fermentation and the fermentation of soybean residue with A. niger has no impact on the height of vili ileum, but it increase the width of vili ileum and apical vili duedenum intestin of local chickens. ____________________________________________________________________________________________________________________ Key words: chicken, soybean residue, fermentation, small intestine